(untitled) (Research, Society and Development, 2022)
Objective: This research aims to describe the experiences of implementing an educational group for patients with hypertension and diabetes mellitus during the covid-19 pandemic period. Methodology: The study consists of an experience report of the researcher, through participant observation. Results: The monitoring of chronic patients through the educational group brought about a greater bonding of patients, improved adherence to treatment, improved health promotion actions by the team, greater accountability of the patient for their care and consequent improvement in the quality of life of the participants. Furthermore, the implementation of the educational group became an instrument for the follow-up of chronic patients by the Family Health Team. Conclusion: The identification of experiences in the organization and implementation of the educational group for chronically ill patients is of paramount importance for sharing actions that can help improve patient care in Primary Health Care.